Workplace health promotion (WHP) : employees' behaviour on smoke-free policy at Universiti Sains Malaysia - Kamaruzzaman Abdul Manan (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
Workplace smoke-free policy has been identified by World Health Organisation as one of the effective strategies in smoking cessation. In today's competitive business world, employees' health status can be a significant factor in driving both individual and organisational successes. Hence, this research seeks to identify the employees' behaviour towards the legislation of USM's smoke-free policy. Another primary focus of this research is to revisit the Theory of Planned Behaviour and specifically takes a close look at how background knowledge variables, namely comprehensive smoke-free workplace, strategic health communication and tobacco hazard influence the employees' attitude towards the policy. The study adopted a quantitative research design. A self-administered questionnaire was distributed to 400 employees (212 males and 188 females). The respondents were selected from a systematic stratified random sampling. The research used survey as the method and questionnaire instrument for data collection. The data collected are related to the respondents' knowledge, attitude and behaviour on USM's smoke-free policy. The findings indicate that in general, employees have a high knowledge, favourable attitude and positive behaviour towards the policy. This indicates that employees are positive with the legislation of USM smoke-free policy. In addition, the strategic health communication is also found to be the most important factor in influencing employees' attitude. This study also found positive relationships between the background knowledge variables and attitude. Moreover, attitude, subjective norms, perceived behavioural control, behavioural intention and behaviour are also positively correlated. Specifically, strategic health communication is found to be the best predictor of attitude and followed by tobacco hazard. In addition, only attitude and perceived behavioural control have the influence towards behavioural intention to comply with smoke-free policy. The research successfully achieves all of its seven research objectives as well as all of its 13 research hypotheses. These research findings indicate that legislation of USM's smoke-free policy is successfully conducted. Moreover, the results manage to contribute towards the body of knowledge in addressing smoking as one of the problems of the employees and achieve the objectives of smoke-free of the organisational society. The generated results can be used for USM smoke-free policy improvement, at present and in the future. Similarly, this research can also be utilised as a yardstick for other organisations in implementing workplace smoke-free policy.